(Des)Encontros na educação matemática escolar: a EJAI a partir das exterioridades coloniais - Endrika Leal Soares (2024)
In this thesis, we aim to problematize the literacy processes of students enrolled in the Education for Young, Adult, and Elderly People modality in a school in the Municipal Education Network of Campo Grande/MS. Amidst the Covid-19 pandemic, we followed classes that took place remotely and later, in person. We worked with the production of narratives involving four students from the class where the research was conducted. The creation of narratives from interview situations was carried out using Oral History methodology. We chose to conceptualize this research from a decolonial perspective, viewing it as movements that assist us in discussions regarding a colonial power matrix operating in the world. This perspective has proven powerful in problematizing the context of Education for Young, Adult, and Elderly People alongside the ideas of Paulo Freire, with whom we have also engaged in dialogue. Consequently, we engage in a process of reflection on the externalities produced in a colonial society and the (im)possibilities of disobedience within these externalities, and how this permeates a literacy class within Education for Young, Adult, and Elderly People. This reflection highlights factors of significant understanding, such as the silencing of individual and collective experiences by the educational system, which operates in service to a modern/colonial society in shaping the mindset of the marginalized. Additionally, it underscores the disobedience of the students towards the school's logic and hegemonic discourses, affirming alternative possibilities of existence in the world, within the realm of both school and mathematics.